2015
DOI: 10.1007/s11240-015-0809-0
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of MpCYS2, a phytocystatin gene from Malus prunifolia (Willd.) Borkh., confers drought tolerance and protects against oxidative stress in Arabidopsis

Abstract: Cystatins, or phytocystatins, are plant-specific inhibitors of cysteine proteinases that help regulate endogenous processes and protect plants against heat, salinity, cold, water deficits, chilling, and abscisic acid treatment. MpCYS2, a cystatin gene from Malus prunifolia, localized to the nucleus, cytoplasm, and plasma membrane in onion epidermal cells. Controlled by the 35S promoter, its ectopic expression in transgenic Arabidopsis lines caused accelerated seed germination and greater seedling growth when p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Prior studies have shown that transgenic plants that have an expanded RSA have improved water homeostasis (Hetherington & Woodward, ; Malamy, ; Masle, Gilmore, & Farquhar, ; Yu et al, ). As a major environmental stress, drought imposes adverse effects on plant growth and development (Denby & Gehring, ; Liu, Qin, Han, Xiang, & Zhao, ; Tan, Li, & Ma, ). Plants need to reallocate energy to increase stress tolerance, and they adjust growth and development during stress‐inducing conditions (Ahuja, de Vos, Bones, & Hall, ; Skircyz & Inzé, ) using diverse mechanisms for coping at the morphological, anatomical, and cellular levels (Bray, ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that transgenic plants that have an expanded RSA have improved water homeostasis (Hetherington & Woodward, ; Malamy, ; Masle, Gilmore, & Farquhar, ; Yu et al, ). As a major environmental stress, drought imposes adverse effects on plant growth and development (Denby & Gehring, ; Liu, Qin, Han, Xiang, & Zhao, ; Tan, Li, & Ma, ). Plants need to reallocate energy to increase stress tolerance, and they adjust growth and development during stress‐inducing conditions (Ahuja, de Vos, Bones, & Hall, ; Skircyz & Inzé, ) using diverse mechanisms for coping at the morphological, anatomical, and cellular levels (Bray, ).…”
Section: Discussionmentioning
confidence: 99%
“…To examine transient expression, we transformed the plasmids into onion epidermal cells with a biolistic helium gun device (PDS-1000; BioRad, Hercules, CA, USA). Cell culturing and fluorescence observations were conducted as previously described 47 . These constructs were also transiently expressed in Arabidopsis protoplasts via polyethylene glycol-mediated transformation based on a protocol previously described 48 .…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, Yadav et al (2016) developed transgenic tobacco plants overexpressing the Arabidopsis annexin gene (AnnAt8) and demonstrated higher chlorophyll retention in transgenic plants than the WT after treatment with 300 mM and 400 mM NaCl. Tan et al (2015) also demonstrated higher chlorophyll content in transgenic Arabidopsis plants overexpressing a novel cystatin gene from Malus prunifolia (MpCYS5) when compared with the WT in the presence of 200 mM NaCl.…”
Section: Response Of T1 Progenies To Salt Stressmentioning
confidence: 92%